The Use of PMC Wagner in Various Missions in the Middle East and Eastern Europe - Fudhali, Aufa Rabbi; Qosim, Ahmad Afrizal (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
Private military contractors and companies (PMCs) are often used to fill empty spaces in the security sector that are not fully facilitated by the state or even not provided. For this reason, adding this space is a good chance for the PMC business. Wagner, a PMC from Russia whose composition ranges from ex-military to foreign legion, has a special role in securing state assets or maintaining security against terrorism and enemy forces. Unfortunately, it is not uncommon to injure other legitimate parties, for example, when trying to assassinate Ukrainian President Volodymyr Zelenskyy. This can be understood as an illicit private authority. Nonetheless, the market share of Wagner PMCs is still in demand and used today, most recently when they were deployed in Syria and Ukraine. This research has the objective of uncovering and answering research questions regarding Wagner's power network and its use in carrying out the mandate to carry out the missions that they were involved in Eastern Europe and the Middle East. Using qualitative methods to be able to see in depth and detail, this paper argues that PMC Wagner exists because it is needed to carry out missions that regular military operators cannot carry out. Many are interested in joining because they get a higher salary than regular army members in the Russian Armed Forces; however, the use of Wagner PMCs is sometimes against the law. This paper concludes that the values carried by PMC Wagner are economically profitable for operators or owners. Renting is also enjoyable because of its success in managing tasks, but there are still legal violations committed, for example, when attacking another sovereign country.